A focus group consultation round exploring patient experiences of comfort during radiotherapy for head and neck cancer. Issue 2 (4th April 2016) - Goldsworthy, Simon D.; Tuke, Kelly; Latour, Jos M.
Abstract: Purpose: The aim of this study was to consult patients about their experiences of comfort while wearing a thermoplastic mask during head and neck radiotherapy before designing a study to develop a comfort scale for radiotherapy. Methods: A qualitative method using a focus group of patients receiving radiotherapy for head and neck cancer was deployed. Five patients were invited and agreed to participate. Semi-structured questions guided the focus group interview. Thematic analysis was used to identify themes. Findings: Three patients participated in the focus group. Three main themes were identified: Physical comfort, Mental perception, Passivity. Physical comfort derived from feelings of pressure, unpleasantness, and generally being uncomfortable. Mental perception derived from how the physical comfort was perceived and derived from feelings of shock, anxiety, indifference and sensory systems. Passivity arose from feelings such as the 'doctor knows best', 'putting up with it', and 'being taken for a ride'. Conclusion: The insight of patient's comfort and experiences are valuable for clinicians to provide patient-centred care. Findings of this study implicate further investigation of how the themes of patient comfort can be measured in radiotherapy to improve the patient experience.